Assessment of Effect of Perceived Social Support on School Readiness, Mental Wellbeing, and Self-Esteem: Mediating Role of Psychological Resilience - Shi, Yefei (Frontiers in Psychology, 2022)
Objective of this study is to investigate the impact of perceived social support on the self esteem, mental well being and school readiness of left behind children. It further aims at understanding the mediating role of psychological resilience between the relationships of perceived social support and self esteem, mental well being and school readiness. For this purpose population frame of the left behind children between the ages of 8-12 years in Mainland, China were taken. The sample size of 335 was taken to reach the findings through partial least square structural equation modeling. The Smart PLS has been used to analyze the data. Results obtained in this study have shown that perceived social support plays a very significant role in enhancing the mental well being, self esteem and school readiness of the left behind children. It has also been found that perceived social support plays a positive role in the psychological resilience. Furthermore, it has also been found that psychological resilience is an important predictor of self esteem and school readiness. Further, the psychological resilience has proved to be significant mediator of between the relationship of perceived social support and self esteem; and also between the relationship of perceived social support and school readiness.